Concept of Prostration in Traditional Malay Mosque Design to the Surrounding Environment with Case Study of Tranquerah Mosque in Malacca, Malaysia - Hassan, Ahmad Sanusi (Journal of Techno-Social, 2010)
This study discusses symbol of prostration concept in the traditional Malay mosque design in Malacca. The literature review covers definition of the keywords, which are sustainable elements, traditional mosque design in Malacca and prostration. The purpose is to identify factors that have significant roles in defining symbol of obedience concept based on Islamic perspectives in the traditional Malay mosque design. In this study, concept of obedience is defined as the acts of prostration to the surrounding environment. The level of prostration is measured based on five Islamic laws as follows; obligation (wajib), desirability (sunat), permissibility (harus), undesirability (makruh) and prohibition (haram). These laws are used as measurable scale in the research analysis to measure the level of prostration in the mosque design. Tranquerah Mosque located in Tranquerah district, Malacca is selected as the case study. This mosque is the oldest mosque in Malacca and second oldest mosque in Malaysia. The analysis shows that the mosque’s symbol of prostration concept is influenced by the local climatic context with reference to comfort and health as the primary indicators. The design elements comprise pyramid roof form, tiered roof system, roof overhangs, roof ridge form, building orientation, open veranda and wall openings.